Clinical Features of Craniopharyngioma With Tumoral Hemorrhage: A Retrospective Case-Controlled Study - Chen, Yusi; Hu, Feng; Wang, Junwen; Huang, Kuan; Liu, Weihua; Tan, Yutang; Zhao, Kai; Xiao, Qungen; Lei, Ting; Shu, Kai (Frontiers in Surgery, 2022)
Background Craniopharyngioma (CP) with tumoral hemorrhage is a very rare syndrome presenting with various manifestation and unfavorable outcomes. The current retrospective study was performed to summarize the clinical features of CP with tumoral hemorrhage. Methods In this study, 185 patients with pathological diagnosis of CP (18 patients with hemorrhage) were enrolled. Clinical characteristics, radiological and surgical treatments, and post-operative complications were analyzed. In addition, the correlations between sexual hormones and tumor volume were explored. Results Drowsiness, acute syndrome, and pituitary deficiency were more frequent in patients with hemorrhage patients. Prothrombin time (PT) were higher in patients with hemorrhage. Luteinizing hormone (LH) and testosterone (T) were lower in male patients with hemorrhage. Post-operative electrolyte disturbances, hypothalamic syndrome, and death appeared more frequently in the hemorrhage group. Moreover, prolactin (PRL) and cortisol 8AM were found to be correlated with the volume of the tumor and the hematoma, respectively. Conclusion The current study presented the clinical features of CP apoplexy from the aspects of clinical characteristics, radiography, surgical treatment, and post-operative complications. Patients with CP apoplexy could benefit from the proper processing of peritumoral hemorrhage and post-operative monitoring of the electrolyte.